DETERMINAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR): SYSTEMATIC LITERATURE REVIEW PERIODE 2023-2026 - Rizka Fajriana Fitri Prasetya; Awaliyatu Khoirunnisa’ (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the determinants of Corporate Social Responsibility (CSR) disclosure using a Systematic Literature Review (SLR) approach for the period 2023–2026. CSR disclosure is an important indicator reflecting corporate transparency and accountability in economic, social, and environmental aspects. This study employs a descriptive qualitative approach using SLR methodology, which consists of planning, conducting, and reporting stages. The data were collected from 20 relevant scientific articles related to CSR disclosure determinants. The results indicate that firm size is as the most dominant and consistent factor influencing CSR disclosure, followed by profitability and leverage, which show inconsistent results. In addition, non-financial factors such as environmental performance, government regulations, audit committees, and media exposure also play a significant role in enhancing CSR disclosure. Meanwhile, variables such as liquidity, ownership structure, earnings management, and board of directors tend to have no significant effect. These findings suggest that CSR disclosure is influenced by a combination of internal and external factors and cannot be explained by a single variable.